Estimating the Stability of Electrical Conductivity of Filled Polymers under the Influence of Negative Temperatures; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Minakova N. N. (2017, 2017)
Title screen